2019
DOI: 10.1016/j.physbeh.2019.112627
|View full text |Cite
|
Sign up to set email alerts
|

Eye region surface temperature dynamics during acute stress relate to baseline glucocorticoids independently of environmental conditions

Abstract: Reactions to acute stressors are critical for survival. Yet, the challenges of assessing underlying physiological processes in the field limit our understanding of how variation in the acute stress response relates to fitness in free-living animals. Glucocorticoid secretion during acute stress can be measured from blood plasma concentrations, but each blood sample can only provide information for one point in time. Also, the number of samples that can be extracted from an individual in the field is usually lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 77 publications
(112 reference statements)
1
51
1
Order By: Relevance
“…The relatively long duration the bill was at a lower temperature on food restricted days compared to food available days indicates that vasoconstriction of the bill was not driven by an acute stress response triggered by the experiment. If so, we would have expected to see a considerably faster return to before-food restriction values than in this study, based on the timeline of the thermal response to an acute stressor in periorbital skin in the closely related blue tit (Cyanistes caeruleus) (Jerem et al, 2019). This provides evidence for selective vasoconstriction of the bill as opposed to a global drop in peripheral temperature as is expected in response to an acute stressor (e.g., Herborn et al, 2015;Nord and Folkow, 2019;Robertson et al, 2020).…”
mentioning
confidence: 68%
“…The relatively long duration the bill was at a lower temperature on food restricted days compared to food available days indicates that vasoconstriction of the bill was not driven by an acute stress response triggered by the experiment. If so, we would have expected to see a considerably faster return to before-food restriction values than in this study, based on the timeline of the thermal response to an acute stressor in periorbital skin in the closely related blue tit (Cyanistes caeruleus) (Jerem et al, 2019). This provides evidence for selective vasoconstriction of the bill as opposed to a global drop in peripheral temperature as is expected in response to an acute stressor (e.g., Herborn et al, 2015;Nord and Folkow, 2019;Robertson et al, 2020).…”
mentioning
confidence: 68%
“…Stress can increase body temperature, known as hyperthermia (Oka, Oka, & Hori, 2001). These increases can occur in as little as 10 s (Bouwknecht, Olivier, & Paylor, 2007; Jerem, Jenni‐Eiermann, McKeegan, McCafferty, & Nager, 2019) and are tuned to stressor intensity (Herborn et al., 2015). Body temperature also appears to be sensitive to longer term factors including personality and time of day (Carere & Van Oers, 2004).…”
Section: Metabolicmentioning
confidence: 99%
“…Body temperature also appears to be sensitive to longer term factors including personality and time of day (Carere & Van Oers, 2004). Finally, eye temperature has been shown to be correlated to baseline circulating glucocorticoids, suggesting it may be a useful biomarker for underlying physiology (Jerem et al., 2018, 2019). Body temperature has promise as a noninvasive indicator of physiological responses to both short (detection within minutes, if not seconds, of stressor onset) and mid‐term stressors (stressor duration up to several days; Figure 1; Table S1), although more validation work is needed.…”
Section: Metabolicmentioning
confidence: 99%
“…shivering and non-shivering thermogenesis in cold, and evaporative cooling in heat; costs reviewed in McKechnie et al, 2016), in favour of self-preservation. Supporting the Thermoprotective Hypothesis, numerous studies have reported an influence of ambient temperature on both the magnitude and direction of stress-induced thermal responses at the skin (Jerem, Jenni-Eiermann, McKeegan, McCafferty, & Nager, 2019;Nord & Folkow, 2019;Robertson et al, 2020;Yokoi, 1966). These studies suggest that such changes may indeed be leveraged for thermoregulatory purposes.…”
Section: Introductionmentioning
confidence: 86%